Settlement quality assessment based on physical and nonphysical aspects: a study case in Prenggan, Kotagede District - Aulia, Nayla Syifa (EDP Sciences, 2023)
The settlements’ quality is closely tied to the degree of ability of a settlement in accessing the inhabitant's needs. If this matter is not considered, it might cause other problems, such as the formation of slum areas. This research contains data based on various aspects, which include economics, accessibility, physical buildings characteristic, sanitation, and living environment. The data were obtained from interviews with 23 respondents in the study area, processed using the Sturgess formula to classify each aspect, and subsequently analyzed using scoring analysis. This research aims to determine the settlement’s quality in Prenggan with the results of various aspects including physical and non-physical from the cluster random sampling interviews. The results from this research regarding settlement quality assessment in part of the Prenggan based on economic aspect is dominated by moderates (60,9), most of the scores on accessibility aspect are low (52,2), the sanitation aspect is dominated by moderate (52,2), the building characteristics aspect where most of the samples lived were classified as high (56,5), and mostly the living environment aspect is high (52,2). This data can be used as a benchmark for the government in designing some development programs that can reduce the area of slums. © 2023 EDP Sciences. All rights reserved.